The Meta-Organism Response of the Environmental Generalist Pocillopora damicornis Exposed to Differential Accumulation of Heat Stress - Bergman, Jessica L.; Leggat, William; Ainsworth, Tracy D. (Frontiers in Marine Science, 2021)
Coral bleaching events in the marine environment are now occurring globally, and the frequency and severity of these events are increasing. Critically, these events can cause the symbiosis between Symbiodiniaceae and their coral hosts to break down, but how the microbial community within the coral responds to bleaching is still equivocal. We investigated the impact of thermal stress exposure on the meta-organism responses of the generalist scleractinian coral species Pocillopora damicornis. Using mesocosms to recreate warming scenarios previously observed at Heron Island, we show that P. damicornis symbiont densities and photophysiological parameters declined at a similar rate under thermal stress regardless of the length of pre-bleaching thermal stress, defined here as temperatures above the monthly maximum mean (MMM) for Heron Island but below the local bleaching threshold (MMM + 2°C). However, we find that the P. damicornis microbiome remains stable over time regardless of the degree of thermal stress and the accumulation of pre-bleaching thermal stress. Our study therefore suggests that while P. damicornis is physiologically impacted by bleaching temperatures, the microbial community identified through 16S rRNA sequencing remains unchanged at the ASV level throughout bleaching. Understanding the capacity of a generalist species to withstand bleaching events is imperative to characterizing what coral species will exist on coral reefs following disturbances, as it has been suggested that the success of environmental generalist species may simplify community structure and lead to changes in biodiversity following environmental disturbance.